2022
DOI: 10.1097/iae.0000000000003304
|View full text |Cite
|
Sign up to set email alerts
|

The Prophylaxis of Fellow-Eye Retinal Detachment in Stickler Syndrome

Abstract: Purpose: To evaluate retrospectively if scleral buckling combined or not to cryopexy reduces fellow-eye retinal detachment (RD) in Stickler syndrome patients who lost their first eye due to RD.Methods: Retrospective review of 52 Stickler syndrome patients who received a 6-mm wide, 360°encircling scleral buckling. Thirty-nine (75%; Cryo + Group) also received cryo treatment, whereas the reminder 13/52 (25% Cryo 2 Group) did not.Results: Average follow-up was 15.6 ± 2.41 years. Five patients (5/52; 9.6%) develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…All of the studies on this topic were retrospective. However, the studies shown in Table 1 demonstrate an overwhelming support for the use of prophylactic retinopexy in these patients [ 11 , 12 , 17 , 18 , 19 , 21 ]. The two case series that reported no benefit after prophylaxis are less persuasive because of the poorly defined patient selection, unspecified treatment protocol and lack of a control group [ 14 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All of the studies on this topic were retrospective. However, the studies shown in Table 1 demonstrate an overwhelming support for the use of prophylactic retinopexy in these patients [ 11 , 12 , 17 , 18 , 19 , 21 ]. The two case series that reported no benefit after prophylaxis are less persuasive because of the poorly defined patient selection, unspecified treatment protocol and lack of a control group [ 14 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Early studies of prophylactic treatment for Stickler syndrome do not provide any details of genetic testing [ 13 , 14 ]. In all reports where genetic confirmation of Stickler syndrome was conducted prior to performing surgical prophylaxis [ 11 , 12 , 17 , 18 , 19 ], the patients had Type 1 Stickler syndrome, caused by mutations in COL2A1. Type 1 disease accounts for around 80% of all cases of Stickler syndrome and represents the majority of cases seen by ophthalmologists [ 16 ].…”
Section: Which Stickler Syndrome Patients Should Receive Prophylaxis?mentioning
confidence: 99%
“…The three common approaches for prophylactic treatment include scleral buckle, laser retinopexy, and cryotherapy retinopexy. Some have even reported combined use of these approaches, for example, use of both cryotherapy and scleral buckle [20]. Others, in particular those who report use of laser retinopexy, employ a variety of laser treatment protocols that make it difficult to compare efficacy of one treatment approach to another.…”
Section: Rationale For Prophylactic Treatmentmentioning
confidence: 99%
“…A recent retrospective case series published in 2022 assessed the impact of prophylactic scleral buckle in patients with genetically confirmed type 1 Stickler syndrome whose fellow eyes had a retinal detachment. All scleral buckles were performed by the same surgeon and used a 6 mm wide encircling band [20]. Thirty-nine patients underwent a scleral buckle with cryotherapy while 13 patients underwent a scleral buckle alone.…”
Section: Scleral Bucklementioning
confidence: 99%
“…Interestingly, in a recent multicentre analysis of affected patients from Korea, splicing variants were the most frequently associated factor with RD (71%) [146]. Although there is no evidence from randomised clinical trials, retrospective reports have suggested that prophylactic cryotherapy and circumferential laser treatment may substantially reduce the risk of RD in STL1 [144,147,148]. Re-detachments are common and often respond well to repeated surgery.…”
Section: Stickler Syndromementioning
confidence: 99%